Natural and anthropogenic influences on the development of mud depocenters in the southwestern Baltic Sea - Lucas Porz; Wenyan Zhang; Corinna Schrum (Oceanologia)
The morphological evolution of two mud depocenters in the southwestern Baltic Sea is investigated by comparison of numerical model results to geological and oceanographic data. The pathways of dense currents during episodic dense-water inflows from the North Sea are shown to correspond to current pathways inferred from contouritic depositional geometries in the flow-confining channels within the study area. A favorable comparison of model results to published current speed observations shows that the mesoscale dynamics of individual inflow events are reproduced by the model, indicating that external forcing and basin geometry rather than internal dynamics control the mesoscale dynamics of inflow events. The bottom current directions during inflows show high stability in the flow-confining channels and explain the contouritic depositional geometries. Asymmetric depositional features in the channels are qualitatively reproduced in the model. Bottom currents are less stable in areas without contouritic features, possibly resulting in an overall diffusive effect on sediment distribution in those areas. In a simulation of resuspension by bottom-contacting fishing gear, inter-basin sediment transport is increased by 4–30%, depending on the area, compared to the case of natural hydrodynamic resuspension. The model predicts an increased winnowing of the finest sediment fraction due to bottom trawling, leading to an overall coarsening-to-fining trend in the direction of net sediment transport. The results show that rather than hemi-pelagic background sedimentation, episodic events with high bottom current velocities as well as bottom-trawling induced resuspension are responsible for the present-day and future morphological configuration of the mud depocenters in the southwestern Baltic Sea.